The functional consequences of social distraction: Attention and memory for complex scenes - Doherty, B; Patai, E; Duta, M; Nobre, A; Scerif, G (Elsevier, 2016)
Cognitive scientists have long proposed that social stimuli attract visual attention even when task irrelevant, but the consequences of this privileged status for memory are unknown. To address this, we combined computational approaches, eye-tracking methodology, and individual-differences measures. Participants searched for targets in scenes containing social or non-social distracters equated for low-level visual salience. Subsequent memory precision for target locations was tested. Individual differences in autistic symptomatology and social anxiety were also measured. Eye-tracking revealed significantly more attentional capture to social compared to non-social distracters. Critically, memory precision for target locations was poorer for social scenes. This effect was moderated by social anxiety, with anxious individuals remembering target locations better under conditions of social distraction. These findings shed further light onto the privileged attentional status of social stimuli and its functional consequences on memory across individuals.